Rotation of crustal domains related to Gondwanide deformation in the Neoproterozoic–Cambrian Sauce Chico Complex (Argentina), southwestern margin of the Río de la Plata Craton: Insights from AMS data - Vazquez Lucero, S.E.; Ballivián Justiniano, C.A.; Fazzito, S.; Prezzi, C.B.; Ruíz González, V.; Rodríguez, S.; Vizán, H. (Precambrian research, 2024)
•Tonian to middle Cambrian rocks crop out at the Sauce Chico Complex, Ventania System.•The studied rocks are controlled by paramagnetic phases, largely secondary sericite.•The crystalline basement is compartmentalized laterally by tear faults.•Strike-slip movements of such faults generated local rotation of blocks.•Differential displacement of blocks could have generated the curvature of the fold belt. The tectonic evolution of the Ventania System fold and thrust belt and the origin of its curvature have been the subject of debates for decades. The Gondwanide Orogeny generated the mylonitization of its Tonian–middle Cambrian basement (i.e., Sauce Chico Complex), accompanied by an intense hydrolysis which produced secondary muscovite (i.e., sericite), and the folding of the overlying Paleozoic sedimentary cover. To evaluate the structural and tectonic evolution of the Ventania System as a result of the interaction of its basement with the Río de la Plata Craton, we studied the anisotropy of magnetic susceptibility (AMS) and rock magnetism on samples of the Sauce Chico Complex. Rock magnetic studies suggest that paramagnetic minerals are the main carriers in the entire Sauce Chico Complex. We suggest that our results reflect secondary muscovite generation due to mylonitization. AMS data reveal that the orientation of the magnetic foliation coincides to a large extent with the rock foliation. However, magnetic and rock foliation orientations are not uniform among the different sampled units, displaying strikes between N 320° (NW) and N 345° (NNW) on average. Localities with different orientations are separated by regional strike-slip structures, referred to as tear faults, which have also been reported and interpreted by previous authors. According to this, we suggest that the variations detected between the orientation of the magnetic and rock foliations of the different basement units may be the result of the rotation of crustal blocks bounded by tear faults. We also propose the existence of a new tear fault not previously recognized. Furthermore, a tear fault of regional character, known as the Sauce Chico Tear Fault, juxtaposes two distinct crustal domains. The differential displacement of such domains could have contributed not only to different structural styles between blocks on both sides of the Sauce Chico Tear Fault, but also to the curved shape of the Ventania System during the progression of the Gondwanide deformation.